(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2018)
Economic and social growth is mutually complimentary. Empirical research shows that merely focus on economic prosperity and social development lead to slower growth and eventually slower growth. Economic sector priority and marginal policy commitment to social sectors such as schooling and health lead to economic growth and social poverty. Social disadvantage, particularly in areas such as education and health, eventually overshadows economic growth and quality of life. In this study we have discussed about the quality management and patient satisfaction, behavioral conflicts in corporate hospitals, concept of services, health care in India, factors attracting corporate to healthcare sector which is concluded that hospitals should focus on the suitable marketing approaches and practices. In order to make patients more patient-friendly, supporting personnel and technicians should be provided with general education in therapeutic areas, such as courtesy and sympathetic treatment.